Gold-catalysed reactions of diynes - Asiri, Abdullah Mohamed; Hashmi, A. Stephen K. (Chemical Society reviews, 2016)
In this critical review the reactivity patterns observed with different types of diyne substrates in gold catalysis are discussed. Apart from the many examples from homogeneous catalysis, the few examples from heterogeneous gold catalysis are also included. With a proper arrangement of the two alkynes unique and exciting reactivity patterns like 1,3-carbonyl transpositions, carbene transfer reactions, cascade annulations, macrocyclisations or the formation of gold vinylidene intermediates are observed. These reactions are of interest for organic synthesis, for pharmaceutical and medicinal chemistry and for material science.
Gesehen am 20.09.2017